Demographic Factors Influencing Work Fatigue Among Medical Personnel at Kartini Hospital, South Jakarta - Pondang, Josafat; Kosasih, Kosasih; Rahmiyati, Ayu Laili (Dinasti International Journal of Education Management and Social Science, 2025)
Fatigue is a common occurrence in the workplace, especially in workplaces that require physical ability and a high level of focus. This condition, which affects workers and can reduce their vitality and productivity, is called occupational fatigue. This study aims to determine the demographic factors (age, gender, length of service, marital status, and education level) that influence occupational fatigue and anxiety among medical personnel at Kartini General Hospital, South Jakarta. The number of respondents taken was 82 medical personnel at Kartini General Hospital using inclusion and exclusion criteria. The research instrument used was the IFRC Questionnaire to assess occupational fatigue. and some demographic data entry using Google Form and tested using the chi-square test The research results showed that factors influencing work fatigue among medical personnel at Kartini Hospital were gender, marital status, and number of shifts.Age, education level, and length of service do not affect work fatigue. Medical personnel with more shifts will experience higher work fatigue. Female medical personnel have higher work fatigue than male medical personnel, and married medical personnel have lower work fatigue than unmarried ones. Gender as a determinant of work fatigue is associated with hormonal and psychological factors, psychological factors, and social factors. Marital status is a determinant factor associated with the role and support of the family towards the individual. A greater number of shifts will increase the workload and is associated with increased work fatigue.